The Effectiveness of BBC Learning English Podcast for EFL Students' Speaking Proficiency: Internet of Things in Digital Pedagogy - Herda, Rozanah Katrina; Del Mundo, Rose Ann; Harahap, Muhammad Fadhly Pratama (Universitas Dian Nuswantoro, 2023)
The rapid growth of the Internet of Things (IoT) in education affected how teachers design teaching scenarios. In speaking classrooms, EFL students face multifaceted dilemmas such as speaking anxiety, lack of vocabulary, and fluency in transferring from L1 to L1. Therefore, digital pedagogy in 21-st century learning demands lifelong learning for students to become active and critical speakers in global communication. This quantitative used a quasi-experimental design involving experiment and control groups to investigate the effect of using BBC Learning English Podcast (BBC LEP) on students' speaking performance. 40 EFL students in a private university in Indonesia were involved in this study. The treatment for the experiment group used BBC LEP to teach speaking, which focused on students' authentic performance in reviewing the news from English podcasts. The data were collected through Pretest and Posttest scores to investigate the significance of the treatment on students' performance. The researchers did normality, homogeneity, and a paired-sample test using SPSS version 25 to analyze the data. The result of the pretest and posttest indicated that teaching speaking using BBC LEP had a significant effect on improving students' speaking skills. Additionally, the study has positive pedagogical impacts for EFL teachers and further researchers who want to conduct teaching speaking by referring to the appropriate treatments linked to the use of English podcasts as the material and media.Keywords: Speaking proficiency; BBC learning English podcast; Internet of things; Digital pedagogy